Study on the Time-lag Failure of Sandstone With Different Degrees of Unloading Damage - Jiang, Qiao; Li, Jianlin; Luo, Zuosen; Xu, Xiaoliang; Assefa, Eleyas; Deng, Huafeng (Periodica Polytechnica Civil Engineering, 2019)
The unloading effect of rock mass excavation is an inevitable practice, and it’s often characterized by a relatively large-scale engineering hazard with a noticeable time lag. A set of unloading triaxial tests were conducted on a sandstone rock to establish the deformation law and the threshold time. Based on the renormalization group theory, the unloading sandstone model was developed by considering the interaction between particles. Similarly, a logistic model was used to predict the unloading damage of sandstone. The unloading time lag damage of sandstone rock was predicted by using the damage threshold. The research shows that: (1) The higher the degree of unloading, the shorter the time-lag failure. (2) The damage range of critical values was optimized. (3) The error between the predicted value and the experimental value of the time threshold was almost less than 5 %, the prediction result was found to be good, and the employed logistic evolution model was reasonable. The findings of this research provide a prediction method and precise information about the mechanism of unloading time lag deformation. Therefore, it can be used as a reference for excavation-support design of underground structures.